Miloš Crnjanski w kręgu polskich odbiorców literatury. Powieść o Londynie, czyli obcość oryginału a obcość przekładu / How Miloš Crnjanski’s works were received by the Polish readers A Novel about London or the strangeness of the original and the strangen - Filipek, Małgorzata (Przekłady Literatur Słowiańskich, 2009)
The 30th anniversary of the death of Miloš Crnjanski (1893—1977) and the publishing of the translation of his novel A Novel about London markt the beginning of studying how the nowel was received by the readers of the original version compared to the readers of the translation with all of its foreign elements. In A Novel about London a reader can easily notice the elements of foreign culture. This leads to the reflection on the differences in how readers of the original version end readers of the translation perceive foreign elements. The different system of connotations is influenced by different language patterns which are typical for the readers of translations. The reading of the Polish version of Crnjanski’s novel let us conclude that the solutions applied by the translator of the foreign text activate the reader’s impression of strangeness which is caused by the presence in the translation of lexical end grammatical categories which are incompatible with the Polish language standards. Nevertheless, the foreign elements of the translation lose their importance when faced with the universality and topical theme of the novel.